Laminin-Coated Electrospun Regenerated Silk Fibroin Mats Promote Neural Progenitor Cell Proliferation, Differentiation, and Survival in vitro - Li, Guangfei; Chen, Kai; You, Dan; Xia, Mingyu; Li, Wen; Fan, Suna; Chai, Renjie; Zhang, Yaopeng; Li, Huawei; Sun, Shan (Frontiers in Bioengineering and Biotechnology, 2019)
Neural progenitor cell (NPC) transplantation is a promising technique for central nervous system (CNS) reconstruction and regeneration. Biomaterial scaffolds, frameworks, and platforms can support NPC proliferation and differentiation in vitro as well as serve as a temporary extracellular matrix after transplantation. However, further applications of biomaterials require improved biological attributes. Silk fibroin (SF), which is produced by Bombyx mori, is a widely used and studied protein polymer for biomaterial application. Here, we prepared aligned and random eletrospun regenerated SF (RSF) scaffolds, and evaluated their impact on the growth of NPCs. First, we isolated NPCs and then cultured them on either laminin-coated RSF mats or conventional laminin-coated coverslips for cell assays. We found that aligned and random RSF led to increases in NPC proliferation of 143.8 ± 13.3% and 156.3 ± 14.7%, respectively, compared to controls. Next, we investigated neuron differentiation and found that the aligned and the random RSF led to increases in increase in neuron differentiation of about 93.2 ± 6.4%, and 3167.1 ± 4.8%, respectively, compared to controls. Furthermore, we measured the survival of NPCs and found that RSF promoted NPC survival, and found there was no difference among those three groups. Finally, signaling pathways in cells cultured on RSF mats were studied for their contributions in neural cell differentiation. Our results indicate that RSF mats provide a functional microenvironment and represent a useful scaffold for the development of new strategies in neural engineering research.